Transporter Selection Based on Supply Chain Management (SCM) Criteria Using Analytical Hierarchy Process (AHP) - chairudin, irwan; Hanifah, Hanifah (STMT Trisakti, 2014)
A company manager should be able to decide which transporter could be used and make sure the product arrives in time to the consumerâs address. It is expected that the manager could choose the transporter based on desired criteria using the method of AHP. Keywords: criteria scm, application of AHP, transporter selection.